Towards the efficient response of forest owners to large-scale forest damage: An example of forest commons - Bogataj, Nevenka; Krč, Janez (Acta geographica Slovenica, 2023)
This article aims to analyse the response of private forest owners to a series of extreme environmental disturbances in the Slovenian karst region in the period 2014–2016. Quantitative and qualitative analysis of empirical forest management data on response time and harvesting time, as well as interpretations of response drivers, led to the identification of forest commons as a fast and efficient type of forest ownership, despite almost a century of state suppression of their local institutions. Among the internal and external response drivers, a norm of responsibility and forest management competence were highlighted. Our study highlights the potential of forest commons for active forest management in Europe. A concerted response from private and state institutions should not only take into account economies of scale, but also traditional knowledge and local social norms